Estimating the Laffer Tax Rate on Capital Income: Cross-Base Responses Matter! - Marie-Noëlle Lefebvre; Etienne Lehmann; Michaël Sicsic (Center for Economic Studies and ifo Institute (CESifo), 2022)
We theoretically express the Laffer tax rate on capital income as a function of the elasticities of capital income (the "direct" elasticity) and of labor income (the "cross" elasticity) with respect to the net-of-tax rate on capital income. We estimate these elasticities using salient capital tax reforms that took place in France between 2008 and 2017. Graphical evidence and Instrumental variables (IV) estimates confirm the existence of significant responses of both capital and labor income to capital tax reforms. Both approaches lead to positive cross responses, in contrast to the prediction of income-shifting models but in line with the two-period "working and saving" model. Cross responses are, however, about ten times lower than direct ones. We obtain a direct elasticity around 0.5 which is robust across specifications. Ignoring the cross elasticity leads to a Laffer rate around 68%. However, since labor incomes are much larger than capital incomes, the Laffer tax rate is especially sensitive to the cross elasticity. Using our estimated positive cross elasticity dramatically reduces the Laffer tax rate on capital income to around 57%, taking only income tax on labor income into account, and down to 35% when we also take payroll taxes into account.
Keywords: H21; H24; H31; C23; C26; 330; capital income taxation; optimal tax; Laffer tax rate; instrumental variables